The gratitude factor enhancing your life through grateful living - Shelton, Charles M. (Mahwah, N.J. : Hidden Spring, 2010)
Helps readers to reflect on the role of gratitude in their lives and to cultivate this virtue for their own benefit. The first author to offer a critique of gratitude through an explanation of various types of gratitude, Charles Shelton uses his skills as a clinical psychologist to present insights into the human experience of gratitude based on his own research. The exercises, strategies, and reflection questions threaded throughout the book give it a practical dimension that facilitates the reader's growth. Shelton's highly original reflection on Jesus as a grateful person lends a spiritual dimension to his work. This book will benefit individual readers as well as serve as a resource for spiritual direction workshops, spiritual formation courses, or ministry formation programs.--From publisher description.
Why gratitude? -- Grateful reasoning -- Exploring gratitude -- Growing in gratitude -- Jesus as God's gratitude and the call to graced goodness -- Glossary : the vocabulary of gratitude.
Includes bibliographical references (p. 170-184).
Description based on print version record.
Keywords: Gratitude -- Religious aspects -- Christianity; RELIGION / Christian Life / General; Electronic books